[Report of the] conference of Amerindian peoples (Guyana Human Rights Association GeorgetownGY, 1987)
Summary of discussions of common problems faced by Amerindian groups in interior of Guyana. These relate to land titles and land tenure, health and social security, transportation, postal service, administration of justice, and the work of churches. Formulates proposals in response to these pressing problems.
IDS